2009
DOI: 10.1016/j.jhydrol.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing soil preferential flow using iodine–starch staining experiments and the active region model

Abstract: Thirteen iodine-starch staining experiments with different boundary conditions and measurement scales were conducted at two sites to study preferential flow processes in natural unsaturated soils. Digital imaging analyses were implemented to obtain the corresponding preferential flow patterns. The test results are used to evaluate a recently proposed active region model in terms of its usefulness and robustness for characterizing unsaturated flow processes at field scale.Test results provide useful insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
3
29
0
2
Order By: Relevance
“…However, the mobile region in the dualdomain model is fixed in the flow process, whereas the active region in the ARM is fractal and changeable, and the relative portion of the active region is expressed as a function of the soil water saturation in the flow region. The treatment of flow region in the ARM is consistent with the field observations (Larsson et al 1999;Liu et al 2005;van Dam et al 1996;Sheng et al 2009). While the previous studies on the ARM mainly focus on its constitutive relationship (Liu et al 2005;Sheng et al 2009), in this study, derivation and evaluation of ARM governing equations are presented for preferential water flow and solute transport in the unsaturated soil.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, the mobile region in the dualdomain model is fixed in the flow process, whereas the active region in the ARM is fractal and changeable, and the relative portion of the active region is expressed as a function of the soil water saturation in the flow region. The treatment of flow region in the ARM is consistent with the field observations (Larsson et al 1999;Liu et al 2005;van Dam et al 1996;Sheng et al 2009). While the previous studies on the ARM mainly focus on its constitutive relationship (Liu et al 2005;Sheng et al 2009), in this study, derivation and evaluation of ARM governing equations are presented for preferential water flow and solute transport in the unsaturated soil.…”
Section: Introductionsupporting
confidence: 73%
“…The ARM is an extension of the active fracture model (AFM) developed for modeling unsaturated flow and transport in the fractured rock (Liu et al 1998(Liu et al , 2003. Sheng et al (2009) demonstrate that the ARM is able to capture the major features of the observed flow patterns under different infiltration conditions, and revealed that ARM parameter (  ) used for describing the flow heterogeneity may be scale independent within their experiment scales.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations